Integrating the Fourth Industrial Revolution into Geotechnical Engineering: Transformations, Challenges, and Future Directions - Firoozi, Ali Akbar; Firoozi, Ali Asghar; Saood Manzar, Mohammad; Khan, Afzal Husain; Vambol, Viola (Ecological Questions, 2025)
The Fourth Industrial Revolution (4IR) heralds a paradigm shift in various sectors, including geotechnical engineering, by introducing advanced technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and robotics. This manuscript delves into the transformative impact of 4IR technologies on geotechnical engineering, highlighting the synergy between traditional practices and cutting-edge innovations. Through a comprehensive review of literature, case studies, and critical analyses, this study explores the integration of 4IR technologies in geotechnical practices, the emergence of geotechnical entrepreneurship, and the pivotal role of interdisciplinary collaboration in driving innovation and sustainability. Additionally, the paper addresses the challenges of adopting 4IR technologies, such as data security, ethical considerations, and educational reform. It concludes with strategic recommendations for future research, development, and adopting 4IR technologies in geotechnical engineering. The scientific value of the current study is to provide stakeholders, policy makers and the academic community with information on the use of 4PR technologies for sustainable, efficient and innovative geotechnical solutions.